Politik Hukum Kerja Sama Penelitian Asing di Indonesia - Nanda Dwi Rizkia; Isis Ikhwansyah; Agus Darmawan (University of Merdeka Malang, 2019)
This study will analyze the law of the political law of research cooperation in Indonesia. The advice used is normative law, to find the rule of law, legal principles, and legal doctrines in responding to the legal issues that are discussed and are happening now. In this case the author is expected to consider the political role of national legal development law in Indonesia which cannot be covered by historical context. Throughout history the Republic of Indonesia has made political changes in the period of the political system as well as the rapid development of science and technology, so that through cooperation with countries abroad is expected to be able to improve the quality of research and publication of research results of Indonesian researchers in journals scientifically reputed internationally.How to cite item: Rizkia, N., Ikhwansyah, I., Darmawan, A. (2019). Politik Hukum Kerja Sama Penelitian Asing di Indonesia. Jurnal Cakrawala Hukum, 10(2), 198-208. doi:https://doi.org/10.26905/idjch.v10i2.3337